Condensation of 2-Substituted 2-Oxazolin-5-ones with o-Hydroxyaromatic Carbonyl Compounds and Their Imines Under Microwave Activation - K. Tripathy, Pradeep (Asian Journal of Chemistry, 2010)
Condensation of 2-substituted 2-oxazolin-5-ones (2) with salicylaldehyde or o-hydroxyacetophenone and/or their N-substituted imines (3) under microwave activation affords 3-N-acylaminocoumarins (5) exclusively, whereas 2-acetoxyaromatic aldehydes (4) produce (Z)-2-substituted-4-(o-acetoxybenzylidene)- 2-oxazolin-5-ones (6). The reaction seems to be initiated by the formation of an adduct through Aldol type condensation at 4-position of the oxazolone ring, followed by intramolecular 1,5-bond cleavage of the ring by the vicinal free -OH group and subsequent ring expansion in the resultant 3-N-acylaminocoumarins (5). It is mentioned here that acetic anhydride mediated cyclocondensation of hippuric acid and salicylaldehyde afforded a mixture of 3-Nbenzoylaminocoumarin (5) and 4-(o-acetoxybenzylidene)-2- phenyl-2-oxazolin-5-one (6) from which coumarin was isolated with low yield as reported in the literature. The present method overcomes all the disadvantages and the solo targeted product can be achieved in a disciplined route. The reaction time is decreased from hours to minute along with a higher yield under microwave irradiation with better purity. All the steps can be carried out in one flask starting from a-N-acylaminoacids (1) under mild and non-hazardous condi-tions using green chemistry methodology.